Anemia Status and Its Related Factors among Indonesian Workers: Hemoglobin Survey in Three Different Workplaces - Chandra, Dian Novita; Pansawira, Pittara; Bardosono, Saptawati (World Nutrition Journal, 2021)
This study aims to explore risk factors of low hemoglobin status (anemia) among workers in three different workplaces in Indonesia. Cross-sectional study design was applied to screen hemoglobin value by using a multiwave pulse total-hemoglobinometer Masimo® and obtain socio-demographic characteristics using a questionnaire. Three workplaces were purposively selected to have total population eligible for this study. Health safety protocol was applied both for the subjects and researchers as COVID19 prevention. Statistical analyses were used accordingly to find potential risk factor(s) of anemia among workers. A total of 2386 eligible subjects with mean age of 36.8 ± 9.2 years participated in this study consisted of mainly male workers (85.3%), mostly married (79.0%), never smoke (55.8%) and working in shift (68.7%). Mean of hemoglobin value was 14.2 ± 1.2 mg/dL with anemia prevalence of 9.9%. Risk factor of anemia among workers were female-gender, non-marriage status, never smoking and no-work shift. However, the potential determinant for anemia among workers was female-gender, in which the prevalence of anemia was 24.6% as compared to 7.4% in male-gender. Keep providing free meal in the workplace canteen is a must, but there is a need to provide iron and vitamin C-fortified food and/or iron and vitamin C supplement especially for female workers.